Social Forestry: The Balance between Welfare and Ecological Justice - Pane, Erina; Yanis, Adam M.; Susanto, Is (International Journal of Criminology and Sociology, 2021)
Poverty and climate change mitigation are connected to each other, so one of the policies adopted by the Indonesian government is managing forests with social forestry schemes. Where social forestry aims at prospering the poor and preserve forests. A balance between the two is needed because it is not only part of forest land, but it also considers justice for the community to get prosperous rights and realize ecological justice. The dynamics of social forestry in Indonesia are characterized by policies and regulations, but in various regions, people have succeeded in increasing their welfare while making forests sustainable. It was concluded that social forestry builds ecological strategic values that guarantee the sustainability of forest functions managed by the community. It can succeed if policies and regulations in Indonesia provide legal certainty over the rights to community-managed forest land.